25-Hydroxycholecalciferol Enhances Male Broiler Breast Meat Yield through the mTOR Pathway. Issue 5 (18th March 2015) - Vignale, Karen; Greene, Elizabeth S; Caldas, Justina V; England, Judith A; Boonsinchai, Nirun; Sodsee, Phiphob; Pollock, Erik D; Dridi, Sami; Coon, Craig N
Abstract: Background: In recent years, there has been a growing body of evidence indicating that replacing cholecalciferol (vitamin D3 ) with 25-hydroxycholecalciferol [25(OH)D3 ] through dietary supplementation enhances breast meat yield in broiler chickens. However, the underlying molecular mechanisms are still unknown. Objective: We investigated the effect of 25(OH)D3 on male broiler growth performance (body weight, feed intake, feed conversion ratio, and breast meat yield), muscle protein synthesis, and the potential underlying molecular mechanisms. Methods: Male Cobb 500 broiler chickens were divided into 4 body weight–matched groups and received a control diet with normal cholecalciferol (2760 IU/kg feed) for 42 d, a diet with high concentrations of cholecalciferol (5520 IU/kg feed) for 42 d, or a diet with 25(OH)D3 (5520 IU/kg feed) for 42 d (HyD-42). A fourth group consumed the HyD-42 for 21 d and then control feed for 21 d (HyD-21) ( n = 360 birds, 12 replicates/treatment). Food and clean water were available for ad libitum consumption. At the end of the 42-d experiment, protein turnover was measured by phenylalanine flooding dose. Breast muscle tissues were collected and protein synthesis–related gene and protein expression were measured by real time polymerase chain reaction and Western blot, respectively. Functional studies were performed in vitro with the use of a quail myoblast (QM7) cell line. QM7 cells were treated with 2 doses (1 nM and 10 nM) of cholecalciferol or 25(OH)D3 alone or in combination with 100 nM rapamycin, and cell proliferation was determined by cell proliferation assay. Protein synthesis–related gene and protein expression were also determined. Results: The HyD-42 increased 25(OH)D3 circulating concentrations by 126% ( P < 0.05), enhanced breast meat yield ( P < 0.05), and increased the fractional rate of protein synthesis by 3-fold ( P < 0.05) compared with the control diet. Molecular analyses revealed that breast muscle from chickens consuming the HyD-42 expressed significantly higher concentrations of vitamin D receptor (VDR), phospho mechanistic target of rapamycin Ser2481, phospho ribosomal P70 S6 kinase (RPS6K) Thr421/Ser424, and antigen Ki-67 (Ki67) compared with the other groups. In line with the in vivo data, in vitro functional studies showed that cells treated with 25(OH)D3 for 24 h had increased VDR expression, and activated the mechanistic target of rapamycin (mTOR)/S6 kinase (S6K) pathway, enhanced Ki67 protein concentrations, and induced QM7 cell proliferation compared with untreated or cholecalciferol-treated cells. Blocking the mTOR pathway with rapamycin reversed these effects. Conclusion: Taken together, our findings provide evidence that the effects of 25(OH)D3 on male broiler breast muscle are likely mediated through the mTOR-S6K pathway.